2021
DOI: 10.3390/nano11051290
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Multiwall Carbon Nanotube Bundles Contacting with Metal Electrodes by Nano Manipulators inside SEM

Abstract: Determining the metallicity and semiconductivity of a multi-walled carbon nanotube (MWCNT) bundle plays a particularly vital role in its interconnection with the metal electrode of an integrated circuit. In this paper, an effective method is proposed to determine the electrical transport properties of an MWCNT bundle using a current–voltage characteristic curve during its electrical breakdown. We established the reliable electrical nanoscale contact between the MWCNT bundle and metal electrode using a robotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Figure 4c,d shows the our PDOS of the first layer of Au atoms and the C atoms nearest to the Au surface. 42 The PDOS of the C atom p orbital and Au atom d orbital has a smaller value near the Fermi level than that of Pt atoms. The strong hybrid orbital was not formed between the p orbital of the C atoms and the d orbital of the first layer of Au atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 4c,d shows the our PDOS of the first layer of Au atoms and the C atoms nearest to the Au surface. 42 The PDOS of the C atom p orbital and Au atom d orbital has a smaller value near the Fermi level than that of Pt atoms. The strong hybrid orbital was not formed between the p orbital of the C atoms and the d orbital of the first layer of Au atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In this case, electrons can easily migrate between compressed CNTs and the Pt surface, which is beneficial for bond forming to reduce contact resistance. Figure c,d shows the our PDOS of the first layer of Au atoms and the C atoms nearest to the Au surface . The PDOS of the C atom p orbital and Au atom d orbital has a smaller value near the Fermi level than that of Pt atoms.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The model consisted of a series structure of contact resistance and CNTB resistance, and the intertube and interwall of MWCNT are parallel structures. There is tunneling resistance between each wall and each tube that can be activated under certain conditions …”
Section: Modelmentioning
confidence: 99%
“…In previous work, the authors demonstrated a nanometrology method based on nanorobotic manipulation inside an SEM chamber to easily manipulate suspended nanostructures. This nanoprobing strategy is relatively easy to assemble and cost-effective, enabling testing of numerous NWs with reduced experimental efforts when examining electrical properties. This is in contrast to conventional electrical characterization methods that employ nanolithography-based techniques for manipulating and establishing electrical contacts with a single NW.…”
Section: Introductionmentioning
confidence: 99%